2013
DOI: 10.1097/rlu.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-Sestamibi Using a Direct Conversion Molecular Breast Imaging System to Assess Tumor Response to Neoadjuvant Chemotherapy in Women With Locally Advanced Breast Cancer

Abstract: Purpose The objective of this study was to determine the ability of breast imaging with 99mTc-sestamibi and a direct conversion–molecular breast imaging (MBI) system to predict early response to neoadjuvant chemotherapy (NAC). Methods Patients undergoing NAC for breast cancer were imaged with a direct conversion–MBI system before (baseline), at 3 to 5 weeks after onset, and after completion of NAC. Tumor size and tumor-to-background (T/B) uptake ratio measured from MBI images were compared with extent of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…The result was even better after the second cycle of NCT, using a cut-off value of 46.4 %, ΔSPECT 2 T/N ratio demonstrated a sensitivity of 92.9 %, a specificity of 93.3 % and a negative predictive value of 93.3 %. Mitchell et al investigated the use of 99m Tc-MIBI imaging to evaluate tumor response to NCT in locally advanced breast cancer [12]. Using a threshold of 50 % reduction in tumor-to-background ratio at 3 to 5 weeks after NCT, 99m Tc-MIBI imaging predicted the presence of residual disease at surgery with a diagnostic accuracy of 89.5 %, a sensitivity of 92.3 %, and a specificity of 83.3 %.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The result was even better after the second cycle of NCT, using a cut-off value of 46.4 %, ΔSPECT 2 T/N ratio demonstrated a sensitivity of 92.9 %, a specificity of 93.3 % and a negative predictive value of 93.3 %. Mitchell et al investigated the use of 99m Tc-MIBI imaging to evaluate tumor response to NCT in locally advanced breast cancer [12]. Using a threshold of 50 % reduction in tumor-to-background ratio at 3 to 5 weeks after NCT, 99m Tc-MIBI imaging predicted the presence of residual disease at surgery with a diagnostic accuracy of 89.5 %, a sensitivity of 92.3 %, and a specificity of 83.3 %.…”
Section: Discussionmentioning
confidence: 98%
“…Functional MRI techniques including dynamic contrast-enhanced MRI, diffusion-weighted imaging and magnetic resonance spectroscopy, provide surrogate markers of response to NCT [8][9][10]. Due to their low cost and wide availability, the use of single photon techniques using MIBI for the early detection of therapy response in breast cancer has also been investigated [11,12]. 99m Tc-3PRGD 2 SPECT is a newly developed imaging modality for evaluating tumor vascular status.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that quantitative assessment of tumor uptake of 99m Tc sestamibi demonstrated the ability to differentiate between pathological responders and non-responders as early as 3–5 weeks after initiation of NAC [36]. To date, there is little understanding of what these changes in tumor uptake represent.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). In a pilot study of 19 patients imaged sequentially with MBI, a decrease in the tumor-tobackground ratio 3-5 wk after the initial round of chemotherapy was shown to predict response to treatment; larger studies are in progress (69). Lack of a substantial decrease in 18 F-FDG uptake after 2 cycles of chemotherapy has been shown to predict residual tumor at the conclusion of chemotherapy and a high risk of recurrence for triple-negative breast cancer (70).…”
Section: Futurementioning
confidence: 99%